The intellectual structure of customer experience research in service scholarship: a bibliometric analysis - Arici, Hasan Evrim; Köseoglu, Mehmet Ali; Sökmen, Alptekin (The Service industries journal, 2022)
This study presents a framework and viewpoint on the intellectual structure and evolution of customer experience research in the service literature. Using the Scopus database, journal articles on customer experience have been extracted and examined to unearth the source knowledge and main themes via a two-step approach of bibliometric (citation and co-citation) and content analyses. The bibliometric analysis has revealed five main clusters of the knowledge domain: (1) methodology and information technology, (2) customer co-creation of value, (3) service quality and customer satisfaction, (4) tourist experience, (5) customer perception in service environments. Based on the literature review, content analysis was subsequently performed to reveal recent articles from each cluster. Overall, this article comprehensively examines customer experience literature in the service industries. Results present a holistic comprehension of the knowledge domain, reveal scientific progress, and provide main directions and questions for further academic efforts.